Experimental determination and practical application of the four-pole parameters of structure-borne sound isolators - MELTZER, G.; MELZIG-THIEL, R. (Archives of Acoustics, 1980)
Theoretical fundamentals are derived for measuring the four-pole para-meters of vibration isolators at real loads. Since the dynamic properties of rubber springs depend on the initial load, the vibration force and velocity are measured on the isolator interfaces for a given initial load. Four-pole parameters are determined for rubber springs and steel springs. The frequency characteristics of the parameters, calculated from the measured results, are compared with the theoretical frequency characteristics. Furthermore, approximate relations for the determination of the four-pole parameters are derived, and verified by experiments. Practical application of the four-pole parameters of vibration isolators is illustrated by examples in which calculations are performed for: structure-borne sound wave isolation by longitudinally vibrating continua and the excitation of structure-borne sound by machines.